Time-frequency analysis : The bilinear Hilbert transform and the Carleson theorem - Oliveira Filho, Itamar Sales de (2016)
In 1966, Lennart Carleson proved that the Fourier series of a periodic function, square integrable over a fundamental domain of the real line converges to the same function almost everywhere. This result was revisited years later by Charles Fe erman (1973) and by Lacey and Thiele (2000). It is studied here Lacey and Thiele's work, where they approached the problem through time-frequency analysis. This proof was inspired in a previous work of theirs, where they establish boundedness for the bilinear Hilbert transform in Lebesgue spaces. The study of boundedness for this operator started with the attempts to establish boundedness for the first Calderon's commutator. Also through time-frequency analysis, it will be studied one of the works of Lacey and Thiele about the bilinear Hilbert transform.